1983
DOI: 10.1007/bf00238309
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of angiotensinogen in rat liver and kidney

Abstract: The renin substrate, angiotensinogen, was localized by immunocytochemistry in liver and kidney of normal rats by the use of an antiserum directed against pure rat angiotensinogen. This substrate was also examined in rats after bilateral nephrectomy, which is known to increase plasma angiotensinogen, and in rats treated with colchicine, which inhibits serum protein secretion. In normal rat liver, light microscopy showed the presence of immunoreactive material in a very few cells. The number of stained hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 25 publications
3
63
0
1
Order By: Relevance
“…47,48,50,52 Proximal tubular cells express mRNA [54][55][56] and protein 53,57 for ACE and Aogen. [58][59][60][61] In vivo evidence that proximal tubular cells may synthesize Ang II has also been reported. 62 The above studies indicate the presence of a functional renal tubular RAAS, which likely has an important function in regulating sodium and fluid balance, and hence BP.…”
Section: Intrarenal Raasmentioning
confidence: 88%
“…47,48,50,52 Proximal tubular cells express mRNA [54][55][56] and protein 53,57 for ACE and Aogen. [58][59][60][61] In vivo evidence that proximal tubular cells may synthesize Ang II has also been reported. 62 The above studies indicate the presence of a functional renal tubular RAAS, which likely has an important function in regulating sodium and fluid balance, and hence BP.…”
Section: Intrarenal Raasmentioning
confidence: 88%
“…Thus, aside from intrarenal vessels, the renin gene is expressed along the proximal tubule, but not in the collecting duct. Since renin substrate and converting enzyme activity is present in proximal tubule cells (6)(7)(8)(9)(10)(11)(12) Figure 6. Autoradiographs of representative renin and /3-actin PCR from CEI treated series.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemical studies have shown the presence of angiotensinogen in the proximal tubule (6), and angiotensinogen mRNA at this site has been detected by in situ hybridization methods, indicating that the renin substrate is, in fact, synthesized by proximal tubule cells (7,8). There also appears to be an abundance of angiotensin converting enzyme in both the apical and basolateral membranes of the proximal tubule (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is difficult to demonstrate angiotensinogen in hepatocytes by immunohistochemistry and to have it found by both in situ hybridization and northern blot analysis, immunohistochemical detection of angiotensinogen has been successfully reported by a few investigators, who treated the rat with bilateral nephrectomy or colchicin injections (MORRIS et al, 1979;RICHoUx et al, 1983;CAMPBELL and HABENER, 1987;GAILLARD-SANCHEZ et al, 1990). Angiotensinogen in human liver is synthesized as a precursor composed of 485 amino acid residures, cleaved into signal peptide composed of 33 amino acid residues and glycosylated angiotensinogen, and then immediately released by a possibly constitutive pathway (DOOLITTLE, 1983;CLAUSER et al, 1989).…”
Section: Circulating Renin-angiotensin Systemmentioning
confidence: 99%